Fishes and Macroinvertebrates of Padawan Limestone, Sarawak, Malaysia - Grinang, Jongkar (Borneo Journal of Resource Science and Technology, 2016)
A survey on fishes and macroinvertebrates was conducted at four streams and a cave passage in the Padawan limestone area of Sarawak, East Malaysia (Borneo). Eighty-four species, comprising 21 fishes, seven crabs, four prawns, 10 snails and 42 aquatic insects were recorded. The finding adds the total species of fishes and crustaceans known from limestone areas in Sarawak to 79 and 29, respectively. Padawan limestone has a similar aquatic fauna with Bau limestone area. Both areas have different species composition from limestone habitats in the northern region of Sarawak. Padawan limestone area has high conservation value, supporting a number of endemic and threatened species, including seven crab and six fish species. Two species of semiterrestrial crabs, Stygothelphusa bidiense and Terrathelphusa kuchingensis are listed as Vulnerable and Endangered, respectively, by the International Union for the Conservation of Nature Red Lists. It was also noted that fishes and a few species of snails serve as important supplement food source for local communities living in the area.